Reverse left ventricular remodeling after aortic valve replacement for aortic stenosis: a systematic review and meta-analysis - Sousa Nunes, F.; Amaral Marques, C.; Isabel Pinho, A.; Sousa-Pinto, B.; Beco, A.; Ricardo Silva, J.; Saraiva, F.; Macedo, F.; Leite-Moreira, A.; Sousa, C. (Frontiers in Cardiovascular Medicine, 2024)
Reverse Left Ventricle (LV) remodeling after Aortic Valve Replacement (AVR), in patients with aortic stenosis, is well-documented as an important prognostic factor. With this systematic review and meta-analysis, we aimed to characterize the response of the unloaded LV after AVR.We searched on MEDLINE/PubMed and Web of Science for studies reporting echocardiographic findings before and at least one month after AVR for the treatment of aortic stenosis. 1836 studies were identified and 1098 were screened for inclusion. The main factors of interest were structural and dynamic measures of the LV and Aortic Valve. We performed a random-effects meta-analysis to compute standardized mean differences (SMD) between follow-up and baseline values for each outcome.Twenty-eight studies met the eligibility criteria, yielding 12234 patients. AVR resulted in reduced